Does Gottman’s Marital Communication Conceptualization Inform Teen Dating Violence? Communication Skill Deficits Analyzed Across Three Samples of Diverse Adolescents - Rueda, Heidi Adams (Journal of interpersonal violence, 2021)
Communication skill deficits are thought to contribute to teen dating violence (TDV), parallel to the inclusion of these throughout prevention curricula. Communication research among adolescents is highly underdeveloped, although a preliminary study utilizing Gottman’s marital communication conceptualization found that a majority of negative communication behaviors predictive of marital distress were also associated with relationship aggression among primarily White college students. Our aim was to replicate this study with diverse samples of adolescents (50.3% Latino, 23.5% Black; Mage = 16.06). Urban high school youth, pregnant and parenting youth in residential foster care, and youth in urban after-school programs self-reported on their use of maladaptive and adaptive communication behaviors, relationship quality (i.e., satisfaction, commitment), and emotional, physical, sexual, relational, and threatening dating violence. Across samples, maladaptive communication and particularly flooding (i.e., the tendency to become overwhelmed, leave the argument) and the four horsemen (i.e., a cascading and negative communication sequence) were associated with higher likelihood of multiple types of TDV. Relationship quality was associated with decreased likelihood for TDV among high school and after-school youth samples, but with increased likelihood among youth in foster care. Results indicate that youth utilize a wide range of both adaptive and maladaptive communication behaviors, and that similar maladaptive patterns predictive of relationship distress in young adulthood and in marriage are also associated with distress in adolescents’ dating relationships. Equipping youth with adaptive communication skills as part of a comprehensive approach to reducing TDV and enhancing healthy relationships is meaningful for diverse adolescents. Further research is warranted concerning youth’s perceptions of relationship quality and risk of TDV.